2017
DOI: 10.1186/s13020-017-0140-2
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activities and mechanisms of heat-clearing and detoxicating traditional Chinese herbal medicine

Abstract: In traditional Chinese medicine (TCM) theory, pathogenic heat and toxins, which are akin to the inflammatory factors, are the causes of cancer and could promote its virulent development. Therefore, heat-clearing and detoxicating (HCD) herbs are essential components of TCM formulas for cancer treatment. An increasing interest has been focused on the study of HCD herbs and accumulated evidences have shown that HCD herbs or HCD herbs-based formulas exhibited remarkable anticancer effects when used alone or combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 99 publications
1
46
0
Order By: Relevance
“…Oridonin gained its attention because of the remarkable properties of growth inhibition and the induction of apoptosis in cancer cells. In vitro and in vivo studies showed the induction of apoptosis in a variety of cancer cells by oridonin as in hepatocellular carcinoma, breast, gastric, skin, colorectal, gallbladder, and pancreatic cancers [112].…”
Section: Rabdosiae Rubescensmentioning
confidence: 99%
“…Oridonin gained its attention because of the remarkable properties of growth inhibition and the induction of apoptosis in cancer cells. In vitro and in vivo studies showed the induction of apoptosis in a variety of cancer cells by oridonin as in hepatocellular carcinoma, breast, gastric, skin, colorectal, gallbladder, and pancreatic cancers [112].…”
Section: Rabdosiae Rubescensmentioning
confidence: 99%
“…Nature products are important source of anti-cancer agents [5][6][7][8]. The genus Ophiorrhiza, a member of Rubiaceae family, is distributed throughout tropical and subtropical Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Complementary medicine has increased 30% in National Cancer Institute (NCI) designated cancer centers, and acupuncture is represented in 73% of those centers, herbal medicine in 66.7% (Yun et al, 2017). Chinese herbs are typically used as an adjuvant therapy, and research suggests the alleviation of clinical symptoms, such as pain, and prolonged survival time of postoperational, and advanced stage cancer patients (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%